2011
DOI: 10.1038/bcj.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a and AMD3100, two ways to control CXCR4 expression in acute myeloid leukemias

Abstract: CXCR4 is a negative prognostic marker in acute myeloid leukemias (AMLs). Therefore, it is necessary to develop novel ways to inhibit CXCR4 expression in leukemia. AMD3100 is an inhibitor of CXCR4 currently used to mobilize cancer cells. CXCR4 is a target of microRNA (miR)-146a that may represent a new tool to inhibit CXCR4 expression. We then investigated CXCR4 regulation by miR-146a in primary AMLs and found an inverse correlation between miR-146a and CXCR4 protein expression levels in all AML subtypes. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 36 publications
5
51
0
1
Order By: Relevance
“…37 Moreover, we also noted that high NRF2 activity caused a decrease in the expression of miRNAs, which includes miR-154, miR146a and miR-181B. All these miRNAs have been shown to be of interest in AML with miR-146a being shown to have low expression in AML, which correlates with high expression of its target gene CXCR4, 38 which in a separate study has been shown to be regulated by NRF2 in human HSC. 39 Consequently in human AML, NRF2 not only regulates key genes involved in the reaction to oxidative stress but also regulates miRNAs that appear to have a broader impact on gene expression and regulation.…”
Section: Discussionmentioning
confidence: 62%
“…37 Moreover, we also noted that high NRF2 activity caused a decrease in the expression of miRNAs, which includes miR-154, miR146a and miR-181B. All these miRNAs have been shown to be of interest in AML with miR-146a being shown to have low expression in AML, which correlates with high expression of its target gene CXCR4, 38 which in a separate study has been shown to be regulated by NRF2 in human HSC. 39 Consequently in human AML, NRF2 not only regulates key genes involved in the reaction to oxidative stress but also regulates miRNAs that appear to have a broader impact on gene expression and regulation.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, the decrease of CXCR4 protein levels observed under severe hypoxia ( Figure 1F) is associated with a marked increase of miR-146a ( Figure 1D) which blocks CXCR4 mRNA translation, according to the previously described mechanism of post-transcriptional control of CXCR4 expression by miR-146a targeting. 39 Altogether, these data show that severe hypoxia impairs monocytic differentiation of hematopoietic progenitor cells and activates miR-146a/CXCR4 regulation to control CXCR4 level. …”
mentioning
confidence: 71%
“…39 We also reported that in acute monocytic leukemia (AML-M5), a high CXCR4 protein level is associated with low/absent miR-146a expression. 39 We then showed that enforced miR-146a expression in leukemic cells decreases the level of CXCR4 protein and improves the sensitivity of these cells to drugs. …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…CXCR4 is a direct target of miR‐150, ‐146a, ‐133 and ‐1 in PCs 57, 61, 64, whereas miR‐23 (miR‐23, ‐24, ‐27) and 221 (miR‐221, ‐222, ‐223) targets SDF‐1α 63, 65, 66. Thereby, up‐regulation of these miRNAs versus miR‐126 in ischaemia respectively represses PC requirement, directional migration and retention of PCs within injured sites 65, 66.…”
Section: Molecular Signatures Associated With Pc Homingmentioning
confidence: 99%